Colorings, cliques and relaxations of planarity - Pinciu, Val (Matemática Contemporânea, 2019)
A conjecture by Albertson states that if χ(G) ≥ n then cr(G) ≥ cr(Kn), where χ(G) is the chromatic number of G and cr(G) is the crossing number of G. This conjecture is true for positive integers n ≤ 16, but it is still open for n ≥ 17. In this paper we consider the statements corresponding to this conjecture where the crossing number of G is replaced with the skewness µ(G) (the minimum number of edges whose removal makes G planar), the genus γ(G) (the minimum genus of the orientable surface on which G is embeddable), and the thickness θ(G) (the minimum number of planar subgraphs of G whose union is G.) We show that the corresponding statements are true for all positive integers n when cr(G) is replaced with µ(G) or γ(G). We also show that the corresponding statement is true for inﬁnitely many values of n, but not for all n, when cr(G) is replaced with θ(G).
Keywords: dept.mat; peer-reviewed; ⛔ No DOI found